Mapping Potential Carbon Content of Seagrass Species as Gas Regulation in Sekotong Waters, West Lombok - Hendra Susana Putra; Agil Al Idrus; Rizal Umami (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Seagrass is one of the ecosystems that absorbs carbon through the process of photosynthesis which can be stored in the form of biomass in the leaves, rhizomes and roots. The content of heavy metal Hg in roots, rhizomes, and leaves of seagrass species has a negative correlation, namely the higher the heavy metal content, the lower the chlorophyll content, which can trigger climate change due to greenhouse gases. The aim of this study was to determine the potential carbon absorption capacity of seagrass species in Sekotong waters, West Lombok. The research method used _ is descriptive quantitative. Plant samples were collected using the Purposive Random Sampling method. Analysis of the carbon content in samples of seagrass species can be identified through C-organic analysis conducted in the laboratory using the Walkley and Black method. The results of the study found that the average Hg and carbon content of seagrass species in seagrass beds were Station 1: (Hg: 0.31, Carbon: 63%), Station 2: (Hg: 0.45, Carbon: 50%) and Station 3: (Hg :0.35%, Carbon:55%). so that it can be concluded that the carbon content in seagrass species decreases with the level of involvement of mercury in seagrass species. The research results are expected to be used as a source of information related to carbon absorption by seagrasses in Sekantung waters, West Lombok so that they can be taken into consideration for the management of water areas, especially the waters of Waring Sekotong, West Lombok.